Farmers' driven improved IPM module brings a better return in bitter gourd - Halder, Jaydeep; Sardana, H R; Pandey, M K; Nagendran, K; Bhat, M N (Indian Horticulture, 2022)
Adaptable and eco-friendly pest management technology for bitter gourd was synthesized, validated, and promoted during 2014-17 at Varanasi, Mirzapur and Deoria districts of eastern Uttar Pradesh in a farmers' led approach. The IPM technology synthesized for bitter gourd crop comprised seed treatment with Trichoderma viride @ 5g/kg of seed; need based spraying of Azadirachtin (0.03%) based neem insecticide @ 5 ml/l for Hadda beetle; installation of cue lure traps (MAT) for fruit flies @ 10/acre; raking of soil for exposing fruit fly pupae to sunlight and predatory fauna and removal of associated weeds, need based application of Bacillus thuringiensis @ 2 g/l against cucumber moth; Azadirachtin 0.03% @ 5 ml/l of water or NSKE 5% for whitefly; systemic fungicide Cymoxanil 8 WP+Mancozeb 64 WP @ 2.5 g/l against downy mildew were found very effective in reducing the incidence of pests and minimizing the yield losses. The IPM plots had lower number of fruit damage (9.60%), Cucumber moth larvae (9.53/plant) and Hadda beetle (2.76/plant) infestations as compared to non-IPM plots (19.10% fruit damage, 20.38 and 6.44, respectively). The adoption of IPM technology also resulted in reducing the number of chemical sprays to 7-10 from 21-25 in non-IPM fields in a season. Moreover, IPM farmers registered higher fruit yield accompanied with average higher net return and higher C:B ratio as compared to the non-IPM farmers.